James Herriot's treasury for children - Herriot, James; Brown, Ruth; Barrett, Peter, 1935- (New York : St. Martin's Press, 1992)
A collection of the author's stories for children, including "Moses the Kitten," "The Market Square Dog," and "Smudge, the Little Lost Lamb."
5.7
3-6
3-6
Keywords: Pets -- England -- Yorkshire -- Biography -- Juvenile literature; Domestic animals -- England -- Yorkshire -- Biography -- Juvenile literature; Farm life -- England -- Yorkshire -- Juvenile literature; Animals; Farm life; Pets -- Biography; Domestic animals -- Biography; Farm life -- Yorkshire (England)